2019
DOI: 10.1111/jcmm.14148
|View full text |Cite
|
Sign up to set email alerts
|

Atractylenolide II reverses the influence of lncRNA XIST/miR‐30a‐5p/ROR1 axis on chemo‐resistance of colorectal cancer cells

Abstract: This investigation was conducted to elucidate whether atractylenolide II could reverse the role of lnc RNA XIST /miR‐30a‐5p/ ROR 1 axis in modulating chemosensitivity of colorectal cancer cells. We totally collected 294 pairs of colorectal cancer tissues and adjacent normal tissues and also purchased colorectal cancer cell lines and human embryonic kidney cell line. 5‐fluorouracil, cisplatin, mitomycin and adriamycin were designated as the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…For example, lncRNA H19 facilitates liver fibrosis by functioning as a ceRNA to sponge miR‐148a to sustain the expression of ubiquitin‐specific protease 4 (USP4) . Recent studies have suggested that XIST may serve as a ceRNA for miRNAs . In the present study, we investigated whether XIST can act as a ceRNA for miRNAs in HSCs activation and liver fibrosis.…”
Section: Discussionmentioning
confidence: 95%
“…For example, lncRNA H19 facilitates liver fibrosis by functioning as a ceRNA to sponge miR‐148a to sustain the expression of ubiquitin‐specific protease 4 (USP4) . Recent studies have suggested that XIST may serve as a ceRNA for miRNAs . In the present study, we investigated whether XIST can act as a ceRNA for miRNAs in HSCs activation and liver fibrosis.…”
Section: Discussionmentioning
confidence: 95%
“…[17][18][19][20] The other miRNAs, miR-30a-5p, miR-92b-3p, and miR-98-5p are involved in proliferation of CRC cells. [21][22][23] In addition, high expression of miR-92b-3p has previously been related to a prolonged progression-free survival in patients with mCRC treated with combined FOLFOX and bevacizumab. 24 The current study aimed to prospectively validate the predictive value of clinical benefit from systemic treatment of the previously identified miRNA signature in a cohort of patients with extensive mCRC, starting first-line palliative systemic therapy.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, this ATL increased the chemosensitivity of CRC cells to conventional chemotherapeutic drugs including 5-fluorouracil, mitomycin, cisplatin, and Adriamycin, and this was achieved by modulating the lncRNA XIST/miR-30a-3p/ROR 1 axis. 42 Through our investigation, we found that the function of ATL-1 is twofold. On one hand, ATL-1 acted directly on CSCs by suppressing stemness maintenance and promoting CSC apoptosis.…”
Section: Discussionmentioning
confidence: 78%